On Thaicypris panhai gen. et sp. nov., a new herpetocypridine ostracod (Crustacea: Ostracoda: Cyprididae) from Thailand - Savatenalinton , Sukonthip (European Journal of Taxonomy, 2022)
A new genus, Thaicypris gen. nov., in the tribe Herpetocypridini Kaufmann, 1900 of the subfamily Herpetocypridinae Kaufmann, 1900 is established to accommodate a new species from Thailand. The present contribution deals with the description of a new genus and species, Thaicypris panhai gen. et sp. nov., which is mainly characterized by the distinctive and raised, inwardly displaced selvage at the postero-ventral part of the right valve (RV) that is not parallel to the valve margin, the absence of an anterior inner list on the RV, the prominent and elevated double inner list on the posterior part of the left valve, the small and three-segmented Rome organ on the first antenna (A1), the spatulated terminal segment of the maxillular (Mx1) palp, the slender caudal ramus (CR) with long and thin Sp seta, the presence of basal triangle on the CR attachment, and the pointed projection at the terminal segment base of the prehensile palps. The hemipenis of the new genus and species is outstanding, especially the medial lateral shield which has a long, beak-shaped protrusion on the distal part. The discovery of this Thai taxon is the first record of the tribe Herpetocypridini in Thailand and the second species of the tribe in Southeast Asia.